Methylglyoxal-induced glycation changes adipose tissue vascular architecture, flow and expansion, leading to insulin resistance /692/163/2743/2037 /692/308/1426 /13/106 /59 /59/36 article - Rodrigues, Tiago (2017)
This study was supported by Portuguese Foundation for Science and Technology (projectUID/NEU/04539/2013), QREN-COMPETE (project DoIT- Diamarker: a consortium for the discovery of novel biomarker in diabetes), POCI-01-0145-FEDER-007440 and by the Faculty of Medicine, University of Coimbra. T. R. and P. M. are supported by a PhD (SFRH/BD/101172/2014) and a Post-Doc Grant (SFRH/BPD/104881/2014). This study was granted by the Portuguese Society of Diabetology (Portuguese National Prize of Diabetes).